The role of Islam and nationalism in constitutional reforms in the cases of Malaysia and Turkey - Akhmetova, Elmira; Tengku Zainal Abidin, Tengku Ahmad Hazri (2018)
This research analysed the roles of Islam, secularism and nationalism in reforms in the Muslim world in general, and in Malaysia and Turkey in particular. In order to understand the relations between Islam and nationalism, the ideas of Musa Jarullah (1875-1949) from Russia, Said Nursi (1877-1960) and Ziya Gokalp (1876-1924) from Turkey, Burhanuddin al-Helmy, a prominent left-leaning intellectual of pre-independence Malaya, were studied. Islam here is demonstrated as a discursive tradition that has to negotiate with existing ideologies and philosophies such as nationalism, secularism and the emergence of nation-states, and in the process not only shaped the destiny of the final structure of the modern governments but also redefined the meaning and orientation of these ideologies. The research found that, in the way of establishing a secure and balanced world, a faith commitment could be considered as a best way of managing diversity and ethnic conflicts than the secular semi-agnostic approach. It also proposed that, in order to establish a healthy and virtuous society, the collective and individual morality and identity should be constructed on the religious values and principles. The research found that Islamic jurisprudence and ethics should play an effective role in directing the contemporary Islamic political thought towards a model of good governance, while Maqasid al-Shari’ah based on wasatiyyah is a necessary tool to widen the scope of the application of Islamic ethos in the contemporary context.